2007
DOI: 10.1021/ol070588f
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Magnetic Nanoparticle via Cu(I)-Catalyzed Alkyne-azide [2 + 3] Cycloaddition

Abstract: The Cu(I)-catalyzed alkyne-azide [2 + 3] cycloaddition has been demonstrated to be an effective and orthogonal conjugation reaction to covalently immobilize biomolecules on magnetic nanoparticles (MNPs). The azido group on the MNP surface provides better conjugation efficiency with alkynated molecules. Moreover, the C-terminal alkynated protein was site-specifically immobilized on MNP. The protein binding activity presented by site-specific immobilization is higher than that by random amide bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 33 publications
3
50
0
1
Order By: Relevance
“…Similarly low efficiency was reported for CuAAC reactions on other alkynyl-presenting surfaces,30,31,44 and was attributed to steric hindrance 30. During optimization of the reaction conditions, we found that O 2 substantially decreased the yields, likely due to the facile oxidation of Cu + to the catalytically inactive Cu 2+ that may also promote the homocoupling of the adjacent alkynes 45.…”
Section: Resultssupporting
confidence: 77%
“…Similarly low efficiency was reported for CuAAC reactions on other alkynyl-presenting surfaces,30,31,44 and was attributed to steric hindrance 30. During optimization of the reaction conditions, we found that O 2 substantially decreased the yields, likely due to the facile oxidation of Cu + to the catalytically inactive Cu 2+ that may also promote the homocoupling of the adjacent alkynes 45.…”
Section: Resultssupporting
confidence: 77%
“…A more biocompatible CuAAC protocol avoiding the need of organic solvents for effective functionalization of MNP (silica oxide-coated Fe 3 O 4 ) with biologically relevant ligands was described by Lin and coworkers (109). Under reported conditions (CuSO 4 , tris(carboxyethyl)phosphine (TCEP), TBTA, pH 8), mannose, biotin, the FLAG peptide, Tn antigen, and various proteins (EGFP and maltose binding protein (MBP)) were incorporated on the MNP surface and detected using fluorescently labeled antibodies/proteins.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…Carbohydrates can also be attached using the highly selective [3+2] Huisgen cycloaddition reaction (Fig. 2c) [72][73][74]. It was reported that the alkyne derivatized carbohydrate reacting with azide functionalized NPs gave better conjugate efficiency compared to that using alkynated NPs with azide bearing molecules [74].…”
Section: Immobilization Of Carbohydrates Onto Magnetic Npsmentioning
confidence: 99%
“…2c) [72][73][74]. It was reported that the alkyne derivatized carbohydrate reacting with azide functionalized NPs gave better conjugate efficiency compared to that using alkynated NPs with azide bearing molecules [74]. In addition, the high affinity binding between strepavidin and biotin can be utilized by incubating biotinated carbohydrates with strepavidin coated NPs [75,76].…”
Section: Immobilization Of Carbohydrates Onto Magnetic Npsmentioning
confidence: 99%